2008
DOI: 10.2147/opth.s3967
|View full text |Cite
|
Sign up to set email alerts
|

Glial and endothelial blood-retinal barrier responses to amyloid-β in the neural retina of the rat

Abstract: The effects of an intravitreal or subretinal injection of soluble or aggregated forms of Aβ1–42 on retinal nestin-immunoreactivity (−IR) and glial fibrillary acidic protein (GFAP)-IR in astrocytes and Müller glial cells and the integrity of the blood-retinal barrier (BRB) were tested in the in vivo rat vitreal-retinal model. Retinas were exposed for 1, 2, 3, 5 or 30 days. We present novel data demonstrating that aggregated Aβ1–42 up-regulates nestin-IR in astrocytes and Müller cells, with a graded response dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 63 publications
0
41
2
Order By: Relevance
“…To evaluate the degree of glial activation, we used a scoring system based on the extent of GFAP staining [14] that has previously been used by our group [9,11,13].…”
Section: Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the degree of glial activation, we used a scoring system based on the extent of GFAP staining [14] that has previously been used by our group [9,11,13].…”
Section: Animal Studiesmentioning
confidence: 99%
“…The Evans Blue albumin method was used as previously described with some modifications [14][15][16][17] (see ESM Methods). Digital images from different random fields of all retinas were acquired using a confocal laser scanning microscope (FV1000; Olympus) at ×20 using the 561 nm laser line, and each image was recorded with identical beam intensity at a size of 1024 pixels × 1024 pixels.…”
Section: Animal Studiesmentioning
confidence: 99%
“…26 To evaluate the degree of glial activation, we used a scoring system based on extent of GFAP staining 28 which had previously been used by our group. 25,26 Briefly, the scoring system used was as follows: Muller cell endfeet region/GCL only (score 1); Muller cell endfeet region/GCL plus a few proximal processes (score 2); Muller cell endfeet plus many processes, but not extending to the outer nuclear layer (ONL (score 3); Muller cell endfeet plus processes throughout with some in the ONL (score 4); and Muller cell endfeet plus many dark processes from GCL extending to the outer margin of the ONL (score 5).…”
Section: Glial Activationmentioning
confidence: 99%
“…Our investigations to date have suggested that a single intravitreal injection of preaggregated Aβ can precipitate degenerative changes in multiple interacting cellular systems including neuronal apoptosis, severe glial activation, immune reactivity, and blood retinal barrier breakdown. 6,[22][23][24] The aim of the present study was to clarify the relationship between Aβ aggregation state and neurotoxicity in vivo. To this end, we have compared Aβ 1-42 prepared under conditions that favor either (1) sAβ (monomers and small oligomers), or solutions that have been (2) preincubated for several days to increase fibril formation, or (3) preincubated for an extended period to obtain highly fibrillar Aβ species.…”
mentioning
confidence: 99%
“…A full description of the retinal glial responses to Aβ 1-42 injection observed in these experiments is reported separately. 24 retinal atrophy at 1-month survival…”
mentioning
confidence: 99%